Micro – and nanofibers and liquid crystals for ligth-scattering shutters: Simulation of electrp-optical properties - Almeida, Pedro L. (2015)
This work demonstrates the feasibility of using polymeric micro- and nanofiber-composed films and liquid crystals as electrically switchable scattering light shutters. We present a concept of electro-optic device based on an innovative combination of two mature technologies: optics of nematic liquid crystals and electrospinning of nanofibers. These devices have electric and optical characteristics far superior to other comparable methods. The simulation presented shows results that are highly consistent with those of experiments and that explain the working mechanism of the devices.